Rapid method for determining free and esterified cholesterol in plasma extracts - Benjamin B. Zeitman (Journal of Lipid Research, 1965)
A method has been developed for the quantitative measurement of free and esterified cholesterol in extracts of rat plasma after separation by thin-layer chromatography. As little as 0.2 ml of plasma may be used in the determinations.